The (il) legitimate experts and their impact on manifest and latent social influence on employees educated in distinct socio - historical contexts - Erjona Manushi Sundic; Gabriel Mugny; Alain Quiamzade; Fabrizio Butera (Frontiers in Social Psychology)
This study investigates how socialization in two different educational environments (during and after the communist regime) affects the level of social influence (manifest and latent) of a director on employees. We compared employees educated during and after the communist regime in Albania and measured the influence of a message delivered in an authoritarian vs. democratic style, by a director of a company labeled as expert vs. non-expert. Results showed that employees educated during the communist regime were more influenced at both the latent and manifest level by an authoritarian expert rather than a democratic one, whereas employees educated after the communist regime were influenced only at a latent level by a democratic expert rather than an authoritarian one. No manifest influence appeared on employees educated after the communist regime independently from the leadership style. This study highlights that the influence of leadership style is context-dependent, with early socialization shaping employees' perceptions of legitimacy and determining the levels of both manifest and latent influence.